2017
DOI: 10.1007/s11524-017-0149-y
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Factors Associated with Psychotropic Drug Use in Brazilian Nightclubs

Abstract: The purpose of this study was to identify environmental factors associated with patterns of psychotropic drug use in nightclubs. Mixed methods were used to investigate psychotropic drugs consumption among patrons of 31 nightclubs in São Paulo, Brazil. A total of 1822 patrons at the entrance and exit of the venues and 30 staff members of the nightclubs were interviewed. The observational data were collected through 307 h of observational research using a structured guide to register environmental measures. Psyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
0
3
0
1
Order By: Relevance
“…The music was therefore not likely to be the only attraction for people who had recently used illegal substances. A Brazilian study found that all-you-can-drink service and lighting effects (such as laser and 'disco lights') were associated with illegal substance use [26]. However, the presence of two or more dance floors and a higher number of security professionals were inversely associated with such use.…”
Section: Discussionmentioning
confidence: 99%
“…The music was therefore not likely to be the only attraction for people who had recently used illegal substances. A Brazilian study found that all-you-can-drink service and lighting effects (such as laser and 'disco lights') were associated with illegal substance use [26]. However, the presence of two or more dance floors and a higher number of security professionals were inversely associated with such use.…”
Section: Discussionmentioning
confidence: 99%
“…It is well documented that polydrug use, including both legal and illicit drugs, are frequently used in Brazilian nightclubs (Carlini & Sanchez, 2018; Sañudo, Andreoni, & Sanchez, 2015), including the use of drugs such as ecstasy and lysergic acid diethylamide ( LSD ) (Battisti, Noto, Nappo, & Carlini, 2006; Remy, Buttram, Kurtz, Surratt, & Pechansky, 2017). Factors that have been related to such club alcohol and drug use include all-you-can-drink services and the type of music played (Carlini, Andreoni, & Sanchez, 2017). Such research has suggested that Brazilian nightclub settings facilitate high-risk behaviors through environmental factors, for example, related to alcohol sales and areas for sex (Carlini & Sanchez, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Six studies examined Nightlife, an exosystem motivator. Specifically, the previous research had examined factors such as the nightlife of young adults (Sirilak, 2018) and the nightclub characteristics (Carlini, Andreoni & Sanchez, 2017). All studies excluding Carlini et al (2017) utilized a microsystem data collection approach, with Carlini et al (2017) utilizing a joint micro-exosystem data collection method by interviewing young adults and staff members at nightclub venues as well as collecting observational data of the nightlife environment.…”
Section: Nightlifementioning
confidence: 99%